2013
DOI: 10.1021/jm401049v
|View full text |Cite
|
Sign up to set email alerts
|

Development of DANDYs, New 3,5-Diaryl-7-azaindoles Demonstrating Potent DYRK1A Kinase Inhibitory Activity

Abstract: A series of 3,5-diaryl-1H-pyrrolo[2,3-b]pyridines were synthesized and evaluated for inhibition of DYRKIA kinase in vitro. Derivatives having hydroxy groups on the aryl moieties (2c, 2j-l) demonstrated high inhibitory potencies with Kis in the low nanomolar range. Their methoxy analogues were up to 100 times less active. Docking studies at the ATP binding site suggested that these compounds bind tightly to this site via a network of multiple H-bonds with the peptide backbone. None of the active compounds were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 58 publications
1
48
0
2
Order By: Relevance
“…Additionally, several inhibitors have been synthesized, such as Tg003 ( Muraki et al, 2004 ) and INDY ( Ogawa et al, 2010 ) two benzothiazole derivatives. For example, DANDY, a new 3,5-diaryl-7-azaindole that demonstrates potent inhibition against DYRK1A kinase activity ( Gourdain et al, 2013 ). HCD160 and its derivatives ( Kim N.D. et al, 2006 ; Koo et al, 2009 ), a series of substituted 6-arylquinazolin-4-amines ( Mott et al, 2009 ; Rosenthal et al, 2011 ), a new 3-(6-hydroxyindol-2-yl)-5-(phenyl)pyridine ( Kassis et al, 2011 ), a series of aryl-substituted aminopyrimidines ( Coombs et al, 2013 ), a new 7-substituted pyrido[2′,3′:4,5]furo[3,2-d]pyrimidin-4-amines ( Deau et al, 2013 ), an 8-arylpyrido[30′20′:4,5]thieno[3,2-d]pyrimidin-4-amines ( Loidreau et al, 2015 ), and a series of hydroxybenzothiophene ketones ( Smith et al, 2012 ; Schmitt et al, 2014 ).…”
Section: An Eruption Of Dyrk1a Kinase Inhibitorsmentioning
confidence: 99%
“…Additionally, several inhibitors have been synthesized, such as Tg003 ( Muraki et al, 2004 ) and INDY ( Ogawa et al, 2010 ) two benzothiazole derivatives. For example, DANDY, a new 3,5-diaryl-7-azaindole that demonstrates potent inhibition against DYRK1A kinase activity ( Gourdain et al, 2013 ). HCD160 and its derivatives ( Kim N.D. et al, 2006 ; Koo et al, 2009 ), a series of substituted 6-arylquinazolin-4-amines ( Mott et al, 2009 ; Rosenthal et al, 2011 ), a new 3-(6-hydroxyindol-2-yl)-5-(phenyl)pyridine ( Kassis et al, 2011 ), a series of aryl-substituted aminopyrimidines ( Coombs et al, 2013 ), a new 7-substituted pyrido[2′,3′:4,5]furo[3,2-d]pyrimidin-4-amines ( Deau et al, 2013 ), an 8-arylpyrido[30′20′:4,5]thieno[3,2-d]pyrimidin-4-amines ( Loidreau et al, 2015 ), and a series of hydroxybenzothiophene ketones ( Smith et al, 2012 ; Schmitt et al, 2014 ).…”
Section: An Eruption Of Dyrk1a Kinase Inhibitorsmentioning
confidence: 99%
“…New synthetic inhibitors of DYRK1A activity, with high purity and specificity, have been tested successfully showing recovery of cognition in DS mouse models (Gourdain et al, 2013;Falke et al, 2015;Kim et al, 2016;Neumann et al, 2018). Cognitive restoration with DYRK1A inhibitors was similar to the genetic rescue observed in in adult DS mouse models when one functional copy of…”
Section: Targeting Common Pathways Altered In Ds and Other Neurodevelmentioning
confidence: 66%
“…We recently reported that hydroxy derivatives of 3,5-diaryl-7-azaindoles (DANDYs) were potent, competitive inhibitors of DYRK1A 34 . The di-, tri- and tetrahydroxy diaryl azaindoles I - IV displayed in vitro inhibition of this kinase with IC 50 s in the 3 to 23 nM range (Fig.…”
Section: Introductionmentioning
confidence: 99%